Social work: Information and communication technologies: Development and innovation - Ferreira, J. (The Routledge international handbook of digital social work, 2023)
In this chapter, we systematise information for the expansion of the collaboration model in the field of social intervention with the inclusion of information and communication technologies. We introduce the method of reflexivity centred on professional practices based on the knowledge produced during the COVID-19 emergency period. This was more focused on the technical dimension of the intervention and response process with the aim of improving the services provided to users and the application of person-centred, digital methodologies. The aim is to stimulate reflection on the basic concepts of digital literacy in social work, within the relationship of engagement with digital tools applied to social intervention. A qualitative method was used using documentary analysis of both scientific articles and other technical material such as reports of national studies, statistical data and legal information on the subject. Results are proposed which constitute a critical reflection on the methodological process of digital social intervention in the framework of data protection and the ethical dimensions of social work. The intention is to contribute to knowledge on the promotion of a new reconfiguration of social work identity and practices in the transition towards collaborative action models and digital interprofessional approaches.